SOCIOLOGICAL ANALYSIS OF «GLOBAL RUSSIANS» SOCIOCULTURAL COMMUNITY VALUE SYSTEM - A. A. Demin (Вестник Кемеровского государственного университета, 2015)
The paper is dedicated to the problem of value foundations of sociocultural communities, which is disclosed in the framework of analyses of a particular case. The author uses the survey results of the peculiarities of ―Global Russians‖ community value system, unifying both Russian emigrants and people, aligned with the reference group, the identification image of which is based on the cosmopolitanism ideas. The following sociocultural community exists within the virtual borders by means of close interaction of its representatives in the framework of closed social network (on the basis of Snob media project). ―Global Russians‖ is a bright example of sociocultural community, the appearance of which is caused by the globalization process. The research of the value system of this community relies on the sociopsychological approach, analyzing the axiological component as the result of person‘s internal experience. The research has an integrated nature and relies on the qualitative methods of analysis: the method of R. Inglehart, the word association method and the qualitative content analysis. As part of the study the author discovers the factors, limiting the capability of socio-psychological adaptation to foreign culture as well as its social attractivity. The discovered factors are directly connected to the value invariants, anchored in the consciousness since the earliest periods of development of the personality, namely – in the primary socialization process.